Lycopene in Combination With Sorafenib Additively Inhibits Tumor Metastasis in Mice Xenografted With Lewis Lung Carcinoma Cells - Chan, Ya-Ping; Chuang, Cheng-Hung; Lee, Inn; Yang, Nae-Cherng (Frontiers in Nutrition, 2022)
Cancer metastasis is the leading cause of death in cancer patients. However, it is unclear whether lycopene can act as an adjuvant to increase the anti-metastatic activity of anticancer drugs. Here, we examined the anti-lung-metastatic effects and the mechanism of lycopene in combination with sorafenib in C57BL/6 mice xenografted with Lewis lung carcinoma (LLC) cells. The mice were divided into five groups: (1) tumor control; (2) lycopene (5 mg/kg); (3) sorafenib (30 mg/kg); (4) lycopene (2 mg/kg) + sorafenib (30 mg/kg); (5) lycopene (5 mg/kg) + sorafenib (30 mg/kg). The results showed that lycopene reduced the number of metastatic tumors in the lungs, which was further suppressed by the combined treatment with sorafenib. The activities of MMP-2 and -9 were further inhibited and TIMP-1 and -2, and NM23-H1, the MMPs negative modulators, were further activated in the combined treatment. Mechanistically, we found that lycopene and sorafenib could additively inhibit the mitogen-activated protein kinase (MAPK) pathways, as shown by the protein phosphorylation of ERK1/2, JNK1/2 and p38 were reduced additively. Overall, the present study demonstrates that lycopene in combination with sorafenib additively inhibits the lung metastasis of tumor, indicating lycopene has potential as an adjuvant for sorafenib in cancer treatment.